Religious Internationals in the Modern World
XIV, 383 p.
Keywords: Tracing the emergence of 'Religious Internationals' as a distinctive new phenomenon in world history, this book transforms our understanding of the role of religion in our modern world. Through in-depth studies comparing the experiences of Buddhists, Christians, Hindus, Jews and Muslims, leading experts shed new light on 'global civil society'.